PESTLE Analysis and Sustainable Event Marketing - Evidences from Mount Kinabalu International Climbathon Destination, Borneo - Jamil, Jamaliah (Politeknik Pariwisata NHI Bandung, 2023)
As an industry practitioner, this research strives to explore and engage in intellectual discourse on the current theoretical paradigm practice of sustainable marketing efficiency strategy design for tourism, hospitality establishments, and event staging from the viewpoints of Destination management organisations (DMOs). Critically, this industry-academic writing is committed to contributing to a better interpretation and, possibly, an assessment of the current marketing principle application by highlighting a potential gap between theory (academic) and practice (industry), accompanied by recommendations on holistic marketing, thereby bridging between conventional and sustainable marketing. A systematic qualitative review using explorative content analysis combined with PESTLE feasibility studies of the destination. Approximately 60 journals, book chapters, and relevant newspaper topics, including pertinent literatures, were screened for analysis. The PESTLE approach to DMOs marketing covers direction, product, service, positioning, branding, and niche segmentation. It also explores Muslim-friendly marketing ideas and their role in compelling destination and event hospitality management. The findings provide analytical perspectives of future hallmarks events for developing countries. Furthermore, it presents a distinct and explicit sustainable marketing policy for event marketers, event organisers, DMOs, and relevant bodies to embed sustainable marketing strategy execution in the event hospitality segment. Additionally, it includes an illustration of a sustainable framework for the future Mount Kinabalu International Climbathon (MKIC) event, recommended to the respective DMOs and event organisers.Keywords: Sustainable Marketing Plan; Marketing Design; Destination Management Organisations DMOs; Mount Kinabalu International Climbathon Event (MKIC); PESTLE analysis.